Readability of Annual Reports of Listed South African Companies and the Adoption of Integrated Reporting - Cele, Welekazi (My University, 2014)
Annual reports are an important tool for communicating the well-being of listed companies and providing information on the basis of which stakeholders should be able to make informed economic decisions. However, many studies have shown that many annual reports are written in complex language which renders them difficult to read. Some stakeholders have therefore been hindered from fully utilising information relevant to economic decision-making. Suggestions have been made that management have a tendency to opportunistically use readability to emphasise good performance and obfuscate bad performance. Loss of trust between business and society has resulted. Pressure to build more requirements into business reporting has increased. The idea of simplifying reporting under a consistent banner – Integrated Reporting (IR) - has thus taken centre stage in the global agenda in recent times. South Africa‟s Johannesburg Stock Exchange (JSE) has led the way by making it compulsory for listed companies to either present annual reports in an integrated format or provide an explanation for non-compliance. This research uses standard readability formulas to assess the level of readability of annual reports of listed companies in South African pre-and post the adoption of integrated reporting by the JSE. Furthermore, it establishes whether these reports are written in a style that makes them difficult or easy to read and whether this has improved with the implementation of integrated reporting. The link between profitability and readability levels is also investigated. The Chairperson‟s statement and Review of operations‟ sections of 2009 and 2010 year-end reports of the 40 selected companies listed on the FTSE/JSE Top 40 index were used as narrative passages for readability formula scoring. Repeated measures design was adopted in collecting data and the readability score of each company was measured in both 2009 and 2010. The study found that annual reports ranged from difficult to very difficult levels of readability in 2009 and in 2010. Not enough evidence was obtained to iii suggest that an improvement in readability occurred post implementation of integrated reporting. Furthermore, no persuasive evidence was obtained to suggest a positive correlation between company performance and readability levels. Persuasive evidence was obtained to suggest that larger companies performed better in terms of readability levels in 2010 than they did in 2009 while the reverse was true for smaller companies. The results indicate that listed companies in SA are not communicating effectively to some of the stakeholders and that this was the case even before the implementation of IR. The implications are that the majority of the adult SA population continue to be excluded from making rational economic decisions.
MBA thesis
Keywords: Annual reports; Integrated reporting